Epitope mapping via selection of anti-FVIII antibody-specific phagepresented peptide ligands that mimic the antibody binding sites - Kahle, Joerg; Orlowski, Aleksander; Stichel, Diana; Becker-Peters, Karin; Kabiri, Ali; Healey, John F.; Brettschneider, Kerstin; Naumann, Anja; Scherger, Anna Katharina; Lollar, Pete; Schwabe, Dirk; Königs, Christoph (Thrombosis and Haemostasis, 2015)
The most serious complication in today’s treatment of congenital haemophilia A is the development of neutralising antibodies (inhibitors) against factor VIII (FVIII). Although FVIII inhibitors can be eliminated by immune tolerance induction (ITI) based on repeated administration of high doses of FVIII, 20–30% of patients fail to become tolerant. Persistence of FVIII inhibitors is associated with increased morbidity and mortality. Data from recent studies provide evidence for a potential association between ITI outcome and epitope specificity of FVIII inhibitors. Nevertheless the determination of epitopes and their clinical relevance has not yet been established. In this study a general strategy for the identification of anti-FVIII antibody epitopes in haemophilia A patient plasma was to be demonstrated. Phage-displayed peptide libraries were screened against anti-FVIII antibodies to isolate specific peptides. Peptide specificity was confirmed by FVIII-sensitive ELISA binding. Peptide residues essential for antibody binding were identified by mutational analysis and epitopes were predicted via FVIII homology search. The proposed mapping strategy was validated for the monoclonal murine antibody (mAb) 2–76. Binding studies with FVIII variants confirmed the location of the predicted epitope at the level of individual amino acids. In addition, anti-FVIII antibody-specific peptide ligands were selected for 10 haemophilia A patients with FVIII inhibitors. Detailed epitope mapping for three of them showed binding sites on the A2, A3 and C2 domains. Precise epitope mapping of anti-FVIII antibodies using antibody-specific peptide ligands can be a useful approach to identify antigenic sites on FVIII.
Keywords: Haemophilia A; anti-FVIII antibodies; inhibitors; epitope mapping; phage display